Peningkatan Kemampuan Intelegensi (IQ) Anak Usia Dini Home Schooling Kak Seto Melalui Model Pembelajaran Neurosains berbasis Aplikasi Layanan Bimbingan Konseling - Faisal Rachmat; Seto Mulyadi; Yufiarti (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
Homeschooled children need neuroscience stimulation to improve their intelligence. The neuroscientific stimulation in question is a neuroscience learning model based on the Guidance and Counseling service application. The purpose of the neuroscience learning model based on the Guidance and Counseling service application to improve the IQ of homeschooled children is to train cognitive concentration, memory and creativity when students do learning activities at school, especially direct learning in the classroom. The Guidance and Counseling Service Application is a software that contains a number of services such as Individual Counseling Services, Group Counseling, Mediation, Consultation, Anecdotal Notes, Case Conferences, Home Visits, Reverals and Service Recaps. BK services are activities that can help children achieve maximum IQ development. This study uses a Qualitative Research type with a single subject (SS) approach. Single Subject Research is a reflective study of various actions or interventions carried out by teachers starting from planning to assessment of real interventions in the classroom in the form of teaching and learning activities to improve the learning conditions carried out. the level of Intelligence Ability in cycle 2 was 23 items and the reliability level of Intelligence Ability in baseline 2 was 0.565. the level of neuroscience learning in cycle 2 was 36 items and the reliability level of neuroscience learning in baseline 2 was 0.970. the level of Guidance and Counseling Service Application in cycle 2 was 16 items and the reliability level of Guidance and Counseling Service Application in baseline 2 was 0.683. the regression of fine motor skills through the neuroscience learning model based on Guidance and Counseling service application was 0.926. The effectiveness of the neuroscience learning model based on the BK service application to improve the intelligence of group A students of Early Childhood HKS is -2.394 which is significant 0.048 which is rounded up to 0.05 (Tcount) is greater than the T-table alpha cronbach 0.05 (1.812461) so that the effectiveness of intelligence ability on the neuroscience learning model based on the BK service application tends to be negative or weak.